Antinociceptive and Antioxidant Activity of Zanthoxylum budrunga Wall (Rutaceae) Seeds - Md. Khirul Islam; Nripendra Nath Biswas; Sanjib Saha; Hemayet Hossain; Ismet Ara Jahan; Tanzir Ahmed Khan; Khalijah Awang; Jamil A. Shilpi (The Scientific World Journal)
Different parts of the medicinal plant Zanthoxylum budrunga Wall enjoy a variety of uses in ethnobotanical practice in Bangladesh. In the present study, a number of phytochemical and pharmacological investigations were done on the ethanol extract of Z. budrunga seeds (ZBSE) to evaluate its antinociceptive and antioxidant potential. ZBSE was also subjected to HPLC analysis to detect the presence of some common antioxidants. In acetic acid induced writhing test in mice, ZBSE showed 65.28 and 74.30% inhibition of writhing at the doses of 250 and 500 mg/kg and the results were statistically significant (P<0.001). In hot-plate test, ZBSE raised the pain threshold significantly (P<0.001) throughout the entire observation period. In DPPH scavenging assay, the IC50 of ZBSE was observed at 82.60 μg/mL. The phenolic content was found to be 338.77 mg GAE/100 g of dried plant material. In reducing power assay, ZBSE showed a concentration dependent reducing ability. HPLC analysis indicated the presence of caffeic acid with a concentration of 75.45 mg/100 g ZBSE. Present investigation supported the use of Zanthoxylum budrunga seed in traditional medicine for pain management. Constituents including caffeic acid and other phenolics might have some role in the observed activity.